Assessing the Quantitative Risk of Urban Hydrogen Refueling Station in Seoul, South Korea, Using SAFETI Model - Kwak, Hyunjun; Kim, Minji; Min, Mimi; Park, Byoungjik; Jung, Seungho (Energies, 2024)
Hydrogen refueling stations (HRS) operating at high pressures pose a higher risk of leakage than conventional gas stations. Therefore, in this study, a quantitative risk assessment (QRA) was conducted using DNV-GL SAFETI v.8.9. The impact of the shutoff valve was quantitatively assessed, and step-by-step mitigation was applied to propose the minimum installation requirements for the valve necessary to achieve broadly acceptable risk levels. The QRA includes sequence analysis (CA), individual risk (IR), and societal risk (SR), with accident scenarios consisting of catastrophic ruptures and three leak scenarios. The research results indicate that the application of a dual shutoff valve system resulted in an IR of 7.48 × 10−5, effectively controlling the risk below the as low as reasonably practicable (ALARP) criteria of the Health and Safety Executive (HSE). The SR was analyzed based on the ALARP criteria in the Netherlands, and the application of the dual shutoff valve system effectively controlled the risk below the ALARP criteria. Consequently, this study suggests that applying a dual shutoff valve system with a mitigation value exceeding 1.21 × 10−2 can successfully mitigate the risk of urban hydrogen refueling stations to broadly acceptable levels.
Keywords: Consequence analysis; Fireball; Hydrogen refueling stations; Individual risks; Jet fire; Quantitative risk analysis; SAFETI; Shut-off valves; Societal risks; Vapour cloud explosions; consequence analysis; fireball; hydrogen refueling station; individual risk; jet fire; quantitative risk analysis; SAFETI; societal risk; vapor cloud explosion